Evaluating post-bronchodilator response in well-controlled paediatric severe asthma using hyperpolarised 129Xe-MRI: A pilot study. (April 2021) - Safavi, Shahideh; Munidasa, Samal; Zanette, Brandon; Dai, Ruixue; Stirrat, Elaine; Li, Daniel; Moraes, Theo J.; Subbarao, Padmaja; Santyr, Giles
Abstract: Introduction: Pulmonary function tests (PFTs) are the main objective measures used to assess asthma in children. However, PFTs provide a global measure of lung function. Hyperpolarised xenon-129 magnetic resonance imaging (129Xe-MRI) can assess lung function spatially. This cross-sectional cohort study aimed to evaluate the use of 129Xe-MRI in detecting ventilation abnormalities in children with well-controlled severe asthma pre- and post-bronchodilator (BD). Method: Six healthy children (aged 11 ± 3) and six with well-controlled severe asthma (14 ± 1) underwent spirometry, multiple breath washout (MBW), and 129Xe-MRI. These tests were repeated post-BD in the asthma cohort. Image analysis was performed in MATLAB. Wilcoxon signed-rank test, repeated measures analysis of variance (ANOVA), and Spearman's rank correlation coefficient were used for statistical analysis. Results: A significantly higher number of ventilation defects were found in the asthma cohort pre-BD compared to the healthy participants and post-BD within the asthma cohort (p = 0.02 and 0.01). A greater number of wedge-shaped defects were detected in the asthma cohort pre-BD compared to healthy participants and post-BD within the asthma cohort (p = 0.01 and 0.008, respectively). 129Xe ventilation defect percentage (VDP) and coefficient of variation (CoV) were significantly higher in the asthma cohort pre-BD compared to the healthy cohort (p = 0.006 for both). VDP and CoV were reduced significantly post-BD in the asthma cohort, to a level where there was no longer a significant difference between the two cohorts. Conclusion: 129Xe-MRI is a sensitive marker of ventilation inhomogeneity in paediatric severe asthma and may potentially be used as a biomarker to assess disease progression and therapeutic response. Highlights: 129Xe-MRI was feasible in children with severe asthma. Significant ventilation defects were seen despite well-controlled severe asthma. Significant reduction in ventilation defects was shown post-bronchodilator. 129Xe-MRI may be more sensitive than LCI and FEV1 at detecting ventilation defects. 129Xe-MRI may be used as an imaging biomarker of therapeutic response.